Association between disease progression and depression onset in persons with radiographic knee osteoarthritis. (24th April 2020) - Rathbun, Alan M; Shardell, Michelle D; Ryan, Alice S; Yau, Michelle S; Gallo, Joseph J; Schuler, Megan S; Stuart, Elizabeth A; Hochberg, Marc C
Abstract: Objectives: Osteoarthritis (OA) disease progression may lead to deteriorating psychosocial function, but it is unclear what aspects of disease severity are related to the onset of depression. This study assessed which components of OA disease progression cumulatively contribute to depression onset in persons with radiographic knee OA. Methods: Osteoarthritis Initiative participants ( n  = 1651) with radiographic disease (Kellgren-Lawrence grade ≥2) in one or both knees and below the screening threshold for probable depression [Center for Epidemiological Studies Depression (CES-D) scale <16] at baseline were included. Disease severity was measured from baseline to the third annual follow-up visit using joint space width, 20-meter gait speed, and the Western Ontario and McMaster Universities Osteoarthritis Index pain subscale, each categorized into quintiles. Depression onset (CES-D ≥ 16) was assessed annually at four follow-up visits. Marginal structural models that account for time-dependent confounding and attrition evaluated the association between each time-varying disease severity measure and depression onset. Results: Each disease severity measure exhibited a non-linear relationship concerning the probability of depression onset, with the higher quintiles generally being associated with a larger risk. The highest quintile (relative to the lowest) of joint space width and gait speed were both significantly associated with depression onset. By contrast, none of the higher pain quintiles compared with the lowest were significantly associated with the onset of depression. Conclusion: Faster disease progression as measured by either worsening structural severity or decreasing physical performance corresponds to an increased risk of depression among individuals with radiographic knee OA.